Pengaruh Kegiatan Ekstrakurikuler Bahasa Jepang terhadap Hasil Belajar Siswa SMA N 1 Ambarawa - Waryanti, Sri; Diner, Lispridona (Chi'e: Journal of Japanese Learning and Teaching, 2019)
The purpose of this study was to determine the effect of Japanese language extracurricular on study result of the students of SMA N 1 Ambarawa, and to find out the factors that influenced Japanese extracurricular activities at SMA N 1 Ambarawa.This quantitative descriptive method has a population and samples in this research are students of class X MIPA 4, X MIPA 6, X SOS 3, and X Language who have the results of learning Japanese and participating in Japanese extracurricular activities. The method of data collection is carried out observation sample and documented the activities. The data obtained is calculated using SPSS and produces a value of 0.483, and with N = 53 and a significance level of 5% is 0.266 (0.483 2 0.266). From the results of data processing, there was a contribution of 23.3%, which means that Japanese language extracurricular activities affect the Japanese study result of SMA N 1 Ambarawa students by 23.3%. The biggest factor affecting Japanese extracurricular activities is the student psychological factors in order to add more information about Japanese Leanguage and Culture (97.2%).